Characterization of the selection of medicines for the Brazilian primary health care - Karnikowski, Margô Gomes de Oliveira; Galato, Dayani; Meiners, Micheline Marie Milward de Azevedo; Silva, Emília Vitória da; Gerlack, Letícia Farias; Bós, Ângelo José Gonçalves; Leite, Silvana Nair; Álvares, Juliana; Guibu, Ione Aquemi; Soeiro, Orlando Mario; Costa, Karen Sarmento; Costa, Ediná Alves; et al. (Revista de Saúde Pública, 2017)
OBJECTIVE: To characterize the process of selection of medicines for primary health care in the Brazilian regions. METHODS: This article is part of the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos – Serviços, 2015 (PNAUM – National Survey on Access, Use and Promotion of Rational Use of Medicines – Services, 2015), a cross-sectional study that consisted of an information gathering in a sample of cities in the five regions of Brazil. The data used were collected by interviews with those responsible for pharmaceutical services (PS) (n = 506), professionals responsible for the dispensing of medicines (n = 1,139), and physicians (n = 1,558). To evaluate the difference between ratios, we adopted the Chi-square test for complex samples. The differences between the averages were analyzed in generalized linear models with F-test with Bonferroni correction for multiple comparisons. The analyses considered significant had p≤0.05. RESULTS: The professionals responsible for pharmaceutical services reported non-existence of a formally constituted Pharmacy and Therapeutics Committee (PTC) (12.5%). They claimed to have an updated (80.4%) list of Essential Medicines (85.3%) and being active participants of this process (88.2%). However, in the perception of respondents, the list only partially (70.1%) meets the health demands. Of the interviewed professionals responsible for the dispensing of medicines, only 16.6% were pharmacists; even so, 47.8% reported to know the procedures to change the list. From the perspective of most of these professionals (70.9%), the list meets the health demands of the city. Among physicians, only 27.2% reported to know the procedures to change the list, but 76.5% would have some claim to change it. Most of them reported to base their claims in clinical experiences (80.0%). For 13.0% of them, the list meets the health demands. CONCLUSIONS: As this is the first national survey of characterization of the process of selection of medicines within primary health care, it brings unpublished data for the assessment of policies related to medicines in Brazil